Mechanical properties of unidirectional, porous polymer/ceramic composites for biomedical applications - Jordi Seuba (Elsevier, 2021)
The addition of a ductile phase to a porous ceramic can help overcome the brittleness of ceramics. Yet, most studies so far have focused on the processing and characterization of dense composites. Alternatively, unidirectional pores can improve the strength of porous ceramics. Here we combine the two approaches and show a simple processing strategy to obtain highly porous, unidirectional ceramic/polymer composites. We infiltrated ice-templated porous zirconia scaffolds with a polymer or a polymer solution. After centrifugation and evaporation of the solvent, porous ceramic composites with a porosity greater than 60% were obtained. Our results demonstrate that the addition of a ductile polymer (PCL) can increase both the strength and the toughness of the composites while maintaining a high porosity, whereas a brittle polymer (epoxy) has seemingly no impact on the fracture properties. This approach could provide porous materials that are easier to handle for biomedical applications.